2020
DOI: 10.3389/fpsyt.2020.00420
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Neuroticism on Depressive Symptoms Among Chinese Adolescents: The Mediation Effects of Cognitive Emotion Regulation Strategies

Abstract: Objective: This study aims to explore the multilevel mediation effects of cognitive emotion regulation strategies (CERS) on the link between neuroticism and depressive symptoms among Chinese adolescents. Method: A total of 1,265 Chinese adolescents were surveyed using the Chinese version of the Cognitive Emotion Regulation Questionnaire (CERQ-C), the neuroticism scale of the Chinese children's version of the Eysenck Personality Questionnaire (EPQ-Ck), and the Chinese Children's Depressive symptoms Inventory (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 30 publications
5
22
1
Order By: Relevance
“…The effect of neuroticism on depression is complex, and multiple mediating variables have been investigated. These include catastrophic and anxiety-provoking appraisals [8], cognitive emotion regulation [9], social inhibition [6,10] and perceived stress [11]. Perceived stress, the feelings or thoughts that individuals experience following stressful life events, is independently linked and often precedes the occurrence of depression.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of neuroticism on depression is complex, and multiple mediating variables have been investigated. These include catastrophic and anxiety-provoking appraisals [8], cognitive emotion regulation [9], social inhibition [6,10] and perceived stress [11]. Perceived stress, the feelings or thoughts that individuals experience following stressful life events, is independently linked and often precedes the occurrence of depression.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Chinese adolescents, Chen et al (22) found that the use of more active cognitive coping, both adaptive and maladaptive, was associated with less unprotected sex. Another study surveyed 1,265 Chinese adolescents and found cognitive ER strategies have partial multilevel mediation effects on the link between neuroticism and depressive symptoms (23).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, individuals with neurotic personality are more likely to have negative emotions (such as anxiety, depression, etc.) [ 39 ] and the neuroticism is closely related to CERS. Some studies have found that neuroticism is negatively correlated with adaptive CERS and positively correlated with maladaptive CERS in adolescents [ 40 ] and adults [ 41 ].…”
Section: Introductionmentioning
confidence: 99%